Electrical Cardioversion of Supraventricular Arryhthmia Patient with Septic Shock - Ayu Pramitha (Universitas Airlangga, 2020)
Supraventricular arrythmia (SVA) is a very common cardiac rhythm problem experienced by patients in intensive care unit (ICU), which both pharmacological and non-pharmacological treatment could treat. Recently, electrical cardioversion has been proven in improving haemodynamic and functional status. We report a case of 59 years old female patient with VA and septic shock with unstable haemodynamic that was immediately improved after electrical cardioversion. The electrical cardioversion (preferably biphasic) is identified in the patient with an absence of oppositions and is more suitable in combination with antiarrhythmic agent.